APPLICATION OF AUDIO VISUAL METHOD TO IMPROVE STUDENTS' UNDERSTANDING OF PAI MATERIAL - Ahmad Fuad Abdul Baqi; Fareed Ahmad Obaidy (International Journal of Multidisciplinary Reseach, 2025)
The media has a very important role so that the position of the mass media becomes the main one in society. With the media, oral and written traditions in the learning process can be enriched with media such as audio-visual media, teachers can create various classroom situations, determine teaching methods that will be used in different situations and create a healthy emotional climate among students. In fact, this audio-visual media further helps teachers